Legislazione e ispezione per la salute e la sicurezza dei lavoratori. Efficacia e limiti / Legislation and occupational safety inspection. Efficacy and limits - Tozzi, G.A. (La Medicina del Lavoro, 2009)
Si fornisce un quadro delle dinamiche che stanno modificando i sottosistemi regolamentari e complementari dei servizi ispettivi. Si analizzano i processi di semplificazione, i limiti e le difficoltà dell’introduzione dei Sistemi di Gestione della Salute e Sicurezza sul Lavoro. Si esemplificano le modalità di verifica in sede di elaborazione e di applicazione della legislazione e delle norme tecniche. Si indicano gli approcci per studiare forme, modalità operative ed efficacia dell’ispezione in materia di salute e sicurezza sul lavoro. Legislation and occupational safety inspection. Efficacy and limits Objectives: To provide information regarding Occupational Health and Safety (OHS) Inspections in Europe. Methods and Results: The dynamics that are transforming regulatory subsystems and complementary inspection services are described. Simplification initiatives, the limits and difficulties of applying the different models of Health and Safety Management Systems are discussed. Examples are given on how to evaluate legislation and technical standards during planning and enforcement. Different approaches for studying characteristics, methodologies and efficacy in practice of OHS Inspection are provided. Conclusions: Targeted inspections need to respond to the needs of enterprises and workers. Impartiality must be guaranteed and workers’ participation should be facilitated.